Prayers of the Khrist Bhaktas of Banaras: Devotion at the Confluence of Rivers - San Chirico, Kerry P. C. (Concilium, 2024)
In Varanasi, a hybrid devotional movement constituted by low-castes and Dalits has grown into the thousands, with prayers offered through the ministrations of Catholic priests and nuns. The geographical center of this movement is a Catholic ashram known as Mātṛ Dhām. In the prayers of the Khrist Bhaktas, or "devotees of Christ," we can hear a vocabulary born from the commingling of different streams: vernacular and devotional Hinduism, on the one hand, and Charismatic Catholicism, on the other. This essay examines some of these prayers from a popular song and prayer book while also attending to the people who offer them.